Credit Risk Determinants of Large Banks within the Eurozone Countries, Which ￼Received a EU bailout; and the Effects of the 2008 Global Financial Crisis - Kyriakos, Fialoyiannos (2013)
This thesis is an empirical investigation of the determinants of non-performing loans (credit risk) in large banks within the five Eurozone Countries that received a EU-bailout. Using Panel Data Analysis, the effects that both macroeconomic as well as bank-specific variables have upon bank credit risk are identified, and ultimately a comparison across all five countries examined is drawn. Finally, two more regression models are incorporated for the pre and post crisis periods, in order to perceive whether the 2008 Global financial crisis and the subsequent European sovereign debt crisis, have affected in any way these determinants. The results show that all the macroeconomic variables (GDP, Inflation, Unemployment) as well as two of the microeconomic variables employed (Bank Size, Liquidity) have significant explanatory power upon bank credit risk. Contrary to theory or studies, we find three of the bank-specific variables (Management Efficiency; Spread; Regulatory Capital) not to be correlated with credit risk across the countries and the test period examined. Lastly, the results obtained from the two supplementary models (pre-crisis & post-crisis) show that indeed the Global financial crisis of 2008 has affected the impact that some of the factors examined have upon credit risk, as well as the risk-taking behaviour of banks in those five countries.